A Prospective Evaluation of Intraoperative Indocyanine Green Fluorescence Angiography for Soft Tissue Sarcomas. (August 2021) - Wilke, Benjamin K.; Schultz, Douglas S.; Huayllani, Maria T.; Boczar, Daniel; Spaulding, Aaron C.; Sherman, Courtney; Murray, Peter; Forte, Antonio J.
Abstract : Introduction: Postoperative wound complications after resection of soft-tissue sarcomas are challenging. Indocyanine green (ICG) angiography has previously been used to predict wound complications, but not for soft-tissue sarcomas. We aimed to evaluate whether this technology could help lower wound complications after soft-tissue sarcoma resections. Materials and Methods: We conducted a prospective study from 10/2017 to 9/2019 using ICG angiography during sarcoma resection surgery. Rates of wound complications were compared with a historical control consisting of surgeries before utilization of ICG angiography. Results: A total of 88 patients were included in the study. We found significantly lower rates of infection (11.8% versus 38%; P = 0.03) and wound dehiscence (11.8% versus 42.3%; P = 0.02) in the ICG angiography cohort compared with the historical controls. Conclusion: ICG angiography use during soft-tissue sarcoma resections is promising technology and warrants further investigation to help reduce postoperative complications.